1997
DOI: 10.1002/cjoc.19970150202
|View full text |Cite
|
Sign up to set email alerts
|

A chemical oscillating reaction in NaBrO3‐pyruvic acid‐H2SP4[Ni(Me2[14]1,3‐diene N4)]2+ system

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to the literature [7][8][9][10][11][12][13], the tetraazamacrocyclic complex-catalyzed systems show some features considerably different from those of the classical ones. In this type of BZ system, both tetraazmacrocyclic complex and organic substrate have a marked influence on the oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature [7][8][9][10][11][12][13], the tetraazamacrocyclic complex-catalyzed systems show some features considerably different from those of the classical ones. In this type of BZ system, both tetraazmacrocyclic complex and organic substrate have a marked influence on the oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some organic species like malonic acid [7], gallic acid [8] and pyruvic acid [9][10][11][12][13] can serve as substrates in BZ oscillations with tetraazamacrocyclic complexes of Cu(II) and Ni(II) as catalysts. In order to search for the possibilities that other organic species may participate in this kind of oscillating reactions, we have investigated the behavior of lactic acid, an important metabolite of the Krebs cycle.…”
Section: Introductionmentioning
confidence: 99%